2001
DOI: 10.1105/tpc.010225
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Plant Kinesin-Related Protein Specifically Associates with the Phragmoplast Organelles

Abstract: In higher plants, the formation of the cell plate during cytokinesis requires coordinated microtubule (MT) reorganization and vesicle transport in the phragmoplast. MT-based kinesin motors are important players in both processes. To understand the mechanisms underlying plant cytokinesis, we have identified AtPAKRP2 (for Arabidopsis thaliana phragmoplast-associated kinesin-related protein 2). AtPAKRP2 is an ungrouped N-terminal motor kinesin. It first appeared in a punctate pattern among interzonal MTs during l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 38 publications
3
60
0
Order By: Relevance
“…We have also identified AtPAKRP2, which is exclusively present in the phragmoplast as well (Lee et al, 2001). AtPAKRP2 is another N-terminal motor KRP, but distantly related to reported KRPs.…”
mentioning
confidence: 68%
“…We have also identified AtPAKRP2, which is exclusively present in the phragmoplast as well (Lee et al, 2001). AtPAKRP2 is another N-terminal motor KRP, but distantly related to reported KRPs.…”
mentioning
confidence: 68%
“…STD1 is localized to the phragmoplast midzone and regulates the lateral expansion of the phragmoplast Previous studies have shown that the homologs of STD1, A. thaliana PAKRP2 and P. patens KINID1a and KINID1b, play a crucial role in phragmoplast organization (Lee et al, 2001;Hiwatashi et al, 2008Hiwatashi et al, , 2014. This prompted us to explore the spatial and temporal localization of the STD1 protein during phragmoplast formation in rice.…”
Section: Std1 Encodes a Kinesin-related Protein And Mainly Expresses mentioning
confidence: 99%
“…In this study, we characterized the rice stemless dwarf 1 (std1) mutant, showing a severely dwarfed phenotype, and cloned the responsible gene using a map-based cloning approach. STD1 encodes a kinesin-related protein that is a homolog of the Arabidopsis thaliana PAKRP2 and the Physcomitrella patens (moss) KINID1a and KINID1b (Lee et al, 2001;Hiwatashi et al, 2008Hiwatashi et al, , 2014. Although the function of this kinesin subfamily in phragmoplast organization has been established, the associated effects on growth and development of higher plants have not been reported because of the lack of an Arabidopsis PAKRP2 mutant.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with this concept, a kinesin AtPAKRP2 has been implicated in the transport of the vesicles to the cell plate along the phragmoplast microtubules. (57) However, so far there has been no direct visualization in live plant cells of AtPAKRP2 carrying the vesicles on the microtubular tracks that deliver the membrane material required for the cell plate formation. In addition, dynamin mutants display cytokinetic defects implicating the role of dynamin-mediated vesicle formation in cytokinesis.…”
Section: Construction Of the Cell Plate During Plant Cytokinesismentioning
confidence: 99%